2011
DOI: 10.1161/circulationaha.111.033118
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Delay and Associated Mortality in Patients Transferred With ST-Segment–Elevation Myocardial Infarction

Abstract: Background-Regional ST-segment-elevation myocardial infarction systems are being developed to improve timely access to primary percutaneous coronary intervention (PCI). System delays may diminish the mortality benefit achieved with primary PCI in ST-segment-elevation myocardial infarction patients, but the specific reasons for and clinical impact of delays in patients transferred for PCI are unknown. Methods and Results-This was a prospective, observational study of 2034 patients transferred for primary PCI at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
89
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 35 publications
7
89
0
1
Order By: Relevance
“…Given the retrospective nature of the study and the limitations of the data registry, reasons for individual patient‐related and system‐related delays are unknown. The reason for the delay may be more important than the length of delay in regard to patient outcomes 4. Finally, LA County is primarily urban‐suburban, and therefore these results may not be generalizable to rural areas, where transport times are longer.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Given the retrospective nature of the study and the limitations of the data registry, reasons for individual patient‐related and system‐related delays are unknown. The reason for the delay may be more important than the length of delay in regard to patient outcomes 4. Finally, LA County is primarily urban‐suburban, and therefore these results may not be generalizable to rural areas, where transport times are longer.…”
Section: Discussionmentioning
confidence: 94%
“…Although potential solutions have been proposed,25 prior experience has shown that improving DIDO is difficult, and delay in obtaining transport is a significant contributor. Miedema et al4 evaluated reasons for delay within each time interval. At the referral facility, the most common reason for delay was awaiting transport, affecting 26% of patients and representing 40% of all delays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, delays in referrals are sometimes experienced. In the study above, the authors reported that delays in referral were seen more frequently in referring hospitals (64%) and then in PCI centers (15.7%) and during transfer (12.6%), respectively (19). In another study, considering the direct admissions to a PCI center, the door-balloon time was found to be longer in transferred STEMI patients (20).…”
Section: Discussionmentioning
confidence: 92%
“…It is pointed out that it takes a maximum of 120 minutes to transfer patients from health centers without this capacity or facility to ones with the capacity of PCI, and it is suggested that even patients receiving fibrinolytic therapy be transferred to health centers with a PCI facility within the first 24 hours (18). Miedema et al (19) investigated delays in transfers and related mortality rates for transferred STEMI patients in their study of 2034 diseases, and they found that for patients with door-balloon contact after 120 minutes, the in-hospital mortality rate was higher compared to patients with door-balloon contact before 120 minutes. Accordingly, the transfer of AMI patients seems to be a medicolegal obligation for the province of Mardin.…”
Section: Discussionmentioning
confidence: 99%